(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2019)
The main objective of this study was to evaluate the levels of some trace metals. The state of heavy metal pollution and the mobility of Fe, Mn, Cu, Zn,pb and Cd were studied in Jerpoly regions in the Mediterranean Sea, five surface sediment samples were collected from each region. Methods used to characterize heavy metals in solid phase of the sediments include physical and chemical extraction. using atomic absorption spectrophotometer and to compare metal concentration. The distribution pattern of heavy metals in the sediment follows the sequence: Fe>Pb>Mn> Zn> Cu> Cd revealed that the sediments of Study area have higher concentrations of fe, Zn,Pb while, , Mn,Cu and Cd have lower concentrations than those of other regions. In general, the results revealed very high contamination factor. The results of contamination factors (Table 5) indicated that in thas study Zn, Cu, Mn possess the lowest CFs reflecting lowest contaminated sediments (CF<1). Both Pb and Cd showed low to moderate contamination level of contamination. On the other hand, Sediments of are highly contaminated (CF>6) with Fe. The major role of carbonate as metal carrier is reflected by the positive correlations between Cu, fe with sand. On the other hand, the positive correlation of OM with Cu suggested that OM has an important role in the binding of these elements. The negative correlation of sand with Pb (r = -0.174) indicate that these elements can be easily released by ion exchange processes due to the electrostatic interaction of trace metals as they are weakly bound and is bioavailable to the liquid phase. The study point out that although there were slight variations in the results of the three indices,